Stratal architecture and platform evolution of an early Frasnian syn-tectonic carbonate platform, Canning Basin, Australia - Chow, N.; George, A.; Trinajstic, Kate; Chen, Z. (Blackwell Publishing Ltd, 2013)
Facies architecture and platform evolution of an early Frasnian reef complex in the northern Canning Basin of north-western Australia were strongly controlled by syn-depositional faulting during a phase of basin extension. The margin-attached Hull platform developed on a fault block of Precambrian basement with accommodation largely generated by movement along the Mount Elma Fault Zone. Recognition of major subaerial exposure and flooding surfaces in the Hull platform (from outcrop and drillcore) has enabled comparison of facies associations within a temporal framework and led to identification of three stages of platform evolution. Stage 1 records initial ramp development on the hangingwall dip slope with predominantly deep subtidal conditions that prevented any cyclic facies arrangements. This stage is characterised by basal siliciclastic deposits and a major deepening-upward facies pattern that is capped by a sequence boundary towards the footwall (north-west) and a major flooding surface towards the hangingwall. Stage 2 reflects the bulk of platform aggradation, significant platform growth towards the hangingwall and the development of reef margins and cyclic facies arrangements. Thickening of this stage towards the hangingwall indicates that accommodation was generated by rotation of the fault block and overlying platform. Stage 3 records a major flooding and backstep of the platform margin.The Hull platform illustrates important elements of margin-attached carbonate platforms in a half-graben setting, including: (i) prominent, but limited, coarse siliciclastic input that does not have a major detrimental effect on carbonate production near the rift margin in arid to semi-arid settings; (ii) wedge-shaped accommodation created by syn-depositional rotation of fault blocks and tilting of the hangingwall dip slope, resulting in shallow-water facies and subaerial exposure up-dip of the rotational axis and deeper water facies down-dip; and (iii) evolution of a ramp to rimmed shelf, coincident with a sequence boundary–flooding surface, that is accelerated by tilting of the hangingwall dip slope during fault-block rotation.